The Influence of Product Quality, Brand Image, and Brand Ambassador on Skincare Purchase Decisions with Trust as a Mediating Variable among Generation Z - Pancawati , Marlina; Arbianti, Dahlia (CV. HEI PUBLISHING INDONESIA, 2025)
The study examines Trust as a mediating factor influencing the impact of Product Quality, Brand Image, and Brand Ambassador on skincare Purchase Decisions among Generation Z consumers in Indonesia. Given Gen Z's digital immersion and exposure to influencers, non-functional elements like brand image and ambassador trust are as vital as product quality. Using a quantitative causal-mediation design with 400 Gen Z respondents from Jabodetabek, data were analyzed through PLS-SEM. Results show Product Quality and Brand Image directly and positively influence Trust and Purchase Decisions, while Brand Ambassador affects Purchasing only through Trust. This confirms Trust mediates all relationships significantly, highlighting brand credibility's key role beyond BPOM certification and celebrity endorsement in securing Gen Z loyalty. The study advises skincare brands to balance investments across product quality, brand image, and ambassador engagement strategically.